Here, we are required to identify the dependent and independent variables, the dependency relationship in the situation.
- The independent and dependent variables are the weight of the dog and the amount of food it should respectively.
- The dependency relationship is thus; The amount of food a dog should eat is a function of the weight of the dog
- The dependency relationship using the function notation is; f(x) = {function of x}.
- The independent variable in this situation is the weight of the dog while the amount of food the dog should eat is the dependent variable. The above is evident from the statement; <em>T</em><em>he amount of food a dog should eat depends on the weight of the </em><em>dog</em><em>.</em>
- <em>According</em><em> </em><em>to </em><em>the </em><em>premise</em><em> </em><em>given </em><em>in </em><em>the </em>question, it is evident that the dependency relationship is;. The amount of food a dog should eat is a function of the weight of the dog
- The dependency relationship can be written mathematically using the function notation as;. f(x) = {function of x}.
Read more:
brainly.com/question/11239214
Y = 5
3(3y - 15) is also equal to 9y - 45, which means to find y, you have to divide 45 by 9, which is 5.
The correct answers are: 1/2, 2 and -2.
To get this, factor f(x)
f(x)=2x^3-x^2-8x+4
f(x)= (2x^3-x^2) - (8x -4)
f(x)= (2x-1)(x^2) + (2x-1)(-4)
f(x)= (2x-1)(x^2-4)
f(x)= (2x-1)(x-2)(x+2)
2x-1=0
2x=1
x=1/2
x-2=0
x=2
x+2=0
x=-2
Answer:
Step-by-step explanation:
Yes I would be glad to help you
Answer:
the answer is C. SAS
this option will be the postulate or theorem